Proliferating cell nuclear antigen expression in papillary thyroid carcinoma. Issue 8 (August 1996) - Ando, H; Funahashi, H; Ito, M; Imai, T; Takagi, H
Abstract : AIMS: To correlate the expression of proliferating cell nuclear antigen (PCNA) with various clinicopathological features of papillary thyroid carcinoma. METHODS: Sections from 131 formalin fixed, paraffin wax embedded papillary thyroid carcinomas were stained with a monoclonal antibody (PC10) directed against PCNA using the avidin-biotin immunoperoxidase (ABC) method. PCNA immunoreactivity was based on the PCNA labelling index (LI) following evaluation of at least 1000 tumour cells, and expressed as follows: grade A (LI < 10%), grade B (10% < or = LI < 25%), and grade C (LI > or = 25%). The relation between PCNA expression in these three groups and other clinicopathological factors, such as sex, age, tumour size, nodal metastases, and histological differentiation, were examined. RESULTS: Based on the labelling index, 57 (43.5%) cases were graded as A, 46 (35.1%) as B, and 28 (21.4%) as C. The female-:male ratios were 6.13:1 for group A, 2.83:1 for group B, and 2.11:1 for group C. The mean (SD) ages of the patients were 39.0 (16.1) in group A, 53.5 (14.4) in group B, and 55.8 (13.3) years in group C. The correlation between age and PCNA grade was strongest in women. CONCLUSIONS: PCNA immunoreactivity is correlated with sex and age in patients with papillary thyroid tumours.